2013
DOI: 10.1523/jneurosci.1536-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cone Phosphodiesterase-6 ' Restores Rod Function and Confers Distinct Physiological Properties in the Rod Phosphodiesterase-6 -Deficient rd10 Mouse

Abstract: Phosphodiesterase-6 (PDE6) is the key effector enzyme of the vertebrate phototransduction pathway in rods and cones. Rod PDE6 catalytic core is composed of two distinct subunits, PDE6␣ and PDE6␤, whereas two identical PDE6␣Ј subunits form the cone PDE6 catalytic core. It is not known whether this difference in PDE6 catalytic subunit identity contributes to the functional differences between rods and cones. To address this question, we expressed cone PDE6␣Ј in the photoreceptor cells of the retinal degeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…32 Similarly, in the rd10 mouse (which lacks the rod Pde6b gene), the cone Pde6a 0 subunit was transgenically expressed in the mutant rd10 rods and this rescued the response to light, demonstrating that cone Pde6a 0 can functionally substitute for Pde6ab. 38 These studies suggest that the rod and cone Pde6 catalytic subunits can functionally substitute for one another and our work further implies that the local environment can determine rod and cone coupling. Although the exact mechanism by which rip3 knockdown leads to upregulation of pde6a and pde6b remains to be determined, our data suggest that maintenance of high levels of the nrl transcription factor in cones is crucial to this process.…”
Section: Discussionsupporting
confidence: 58%
“…32 Similarly, in the rd10 mouse (which lacks the rod Pde6b gene), the cone Pde6a 0 subunit was transgenically expressed in the mutant rd10 rods and this rescued the response to light, demonstrating that cone Pde6a 0 can functionally substitute for Pde6ab. 38 These studies suggest that the rod and cone Pde6 catalytic subunits can functionally substitute for one another and our work further implies that the local environment can determine rod and cone coupling. Although the exact mechanism by which rip3 knockdown leads to upregulation of pde6a and pde6b remains to be determined, our data suggest that maintenance of high levels of the nrl transcription factor in cones is crucial to this process.…”
Section: Discussionsupporting
confidence: 58%
“…Conversely, the high affinity binding of Pγ to the α-subunit in the GAFa domain might provide a mechanism for a rapid deactivation of rod PDE6 upon Gα t hydrolysis. Consistent with this idea, ectopic expression of cone PDE6 (which has higher sequence similarity to the β-subunit than the α-subunit) in rod photoreceptors led to nearly two-fold slower deactivation in light responses (51). This asymmetric binding of the inhibitory γ-subunit around the noncatalytic cGMP binding sites in the two GAFa domains of Pαβ likely underlies the previously observed heterogeneity in cGMP binding to Pαβ.…”
Section: Discussionmentioning
confidence: 76%
“…Based on these data and results from this study, we conclude that the configuration of the multisubunit enzyme PDE6 is functionally more interchangeable than previously thought. It was shown that the catalytic cone subunit PDE6C by assembling with the inhibitory PDE6G subunit of rods can restore rod functions in the rod Pde6b-deficient rd10 mouse model (71). Because the catalytic domains of PDE6 are highly conserved among rods and cones, it is not surprising that they may substitute for each other (70 -73).…”
Section: Discussionmentioning
confidence: 99%